(untitled) (Práxis Educativa, 2022)
This article aims to contribute, from the dialogues with studies on whiteness and the theoretical contributions of black feminism, to the field of Education. For that, we start from a qualitative analysis, inspired by oral history, and bring to the scene oral reports from teachers who worked in Basic Education. The data point to the maintenance of the hierarchies imposed by whiteness, and make explicit the racial marks transposed even on the process of flexibilization of gender inequalities. Keywords: Whiteness. Black Feminism. Teaching.